2017
DOI: 10.1017/inp.2017.1
|View full text |Cite
|
Sign up to set email alerts
|

The Expansion Route of Ryegrasses (Lolium spp.) into Sandy Coasts in Japan

Abstract: Although an increasing number of investigations have been made into the evolution of alien species once introduced, few studies have identified the invasion routes of these introduced species. Because multiple introductions are common in invasive species, failing to take into account the introduced lineages can be misleading when studying evolutionary change in alien species after they begin to extend their ranges. In Japan, diverse lineages of ryegrasses (Lolium spp.) were introduced as forage crops and conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…However, although the morphological characteristics of L. multiflorum and L. perenne cultivated in this study matched the taxonomic description of both species in Osada (), the morphology of SP did not match existing descriptions. Our previous study suggested that individuals of the outcrossing Lolium species growing on several coasts were genetically and morphologically different to those growing in adjacent paddy fields where L. multiflorum usually grows, but were similar to those growing around adjacent international seaports (Higuchi, Shimono, & Tominaga, ). This previous study used the same genetic markers and morphological characteristics as the present study.…”
Section: Discussionmentioning
confidence: 97%
“…However, although the morphological characteristics of L. multiflorum and L. perenne cultivated in this study matched the taxonomic description of both species in Osada (), the morphology of SP did not match existing descriptions. Our previous study suggested that individuals of the outcrossing Lolium species growing on several coasts were genetically and morphologically different to those growing in adjacent paddy fields where L. multiflorum usually grows, but were similar to those growing around adjacent international seaports (Higuchi, Shimono, & Tominaga, ). This previous study used the same genetic markers and morphological characteristics as the present study.…”
Section: Discussionmentioning
confidence: 97%
“…Lolium species have naturalised in human-created open areas, such as croplands, abandoned land and roadsides throughout Japan. They are also distributed along the sandy coast of Japan (Higuchi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Lolium species have naturalised in human‐created open areas, such as croplands, abandoned land and roadsides throughout Japan. They are also distributed along the sandy coast of Japan (Higuchi et al., 2017). Abiotic stresses, such as high salinity, sand burial and wind abrasion (Lowry et al., 2008; Ogura & Yura, 2008; Wilson & Sykes, 1999), which are distinctively different from other habitats, are important selective forces on sandy coasts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These weed seeds spill out of grain commodities during unloading, transportation, and usage, and some of them establish successfully (Shimono et al 2015). Moreover, some species derived from grain commodities have become problematic weeds in farmlands and natural habitats (Kurokawa et al 2004;Lehan et al 2013;Higuchi et al 2017). Therefore, the assessment of the role of weed seeds in imported grain commodities as propagule pressure can provide basic information for effective weed management practices and prevention measures for the further introduction of alien species.…”
Section: Introductionmentioning
confidence: 99%